Metagenomic insights into the characteristics of soil microbial communities in the decomposing biomass of Moso bamboo forests under different management practices - Zhang, Xiaoping; Huang, Zhiyuan; Zhong, Zheke; Li, Qiaoling; Bian, Fangyuan; Yang, Chuanbao (Frontiers in Microbiology, 2022)
Considering the rapid growth and high biomass productivity, Moso bamboo (Phyllostachys edulis) has high carbon (C) sequestration potential, and different management practices can strongly modify its C pools. Soil microorganisms play an important role in C turnover through dead plant and microbial biomass degradation. To date, little is known about how different management practices affect microbial carbohydrate-active enzymes (CAZymes) and their responses to dead biomass degradation. This study analyzed three comparable stands from each Moso bamboo plantation: undisturbed (M0), extensively managed (M1), and intensively managed (M2). The results showed that the number of CAZymes encoding plant-derived component degradation was higher than that encoding microbe-derived component degradation. Compared with the M0, the CAZyme families encoding plant-derived cellulose were significantly (p < 0.05) high in M2 and significantly (p < 0.05) low in M1. For microbe-derived components, the abundance of CAZymes involved in the bacterial-derived peptidoglycan was higher than that in fungal-derived components (chitin and glucans). Furthermore, M2 significantly increased the fungal-derived chitin and bacterial-derived peptidoglycan compared to M0, whereas M1 significantly decreased the fungal-derived glucans and significantly increased the bacterial-derived peptidoglycan. Four bacterial phyla (Acidobacteria, Actinobacteria, Proteobacteria, and Chloroflexi) mainly contributed to the degradation of C sources from the plant and microbial biomass. Redundancy analysis (RDA) and mantel test suggested the abundance of CAZyme encoding genes for plant and microbial biomass degradation are significantly correlated with soil pH, total P, and available K. Least Squares Path Modeling (PLS-PM) showed that management practices indirectly affect the CAZyme encoding genes associated with plant and microbial biomass degradation by regulating the soil pH and nutrients (total N and P), respectively. Overall, this study established that M2 and M1 impact dead biomass decomposition and C turnover, contributing to decreased C accumulation and establishing that the bacterial community plays the main role in C turnover in bamboo plantations.